Perception of Teachers Regarding Problem-Based Learning and Traditional Method in the Classroom Learning Innovation Proces - Asti Gumartifa; Indawan Syahri; Rusdy A Siroj; Maftuhah Nurrahmi; Norazmie Yusof (Universitas Muhammadiyah Surakarta, 2023)
The implementation of problem-based learning (PBL) method in the teaching of English at the junior high school level has proven to be beneficial and effective, as evidenced by the research findings. PBL focuses on the learning process itself by incorporating real-world issues and problems that are aligned with the school curriculum. This approach addresses various challenges that may arise during the learning process, such as lack of engagement, learning disabilities, language barriers, limited resources, and teacher-student relationships. Therefore, this research aimed to investigate perception of teachers regarding PBL and traditional method of teaching English at the junior high School level. The research design used was descriptive, and it involved data collection through interviews, as well as analysis. The data were gathered from various English teachers at different Junior High Schools in South Sumatra, with a total of 34 participants. A questionnaire was used to measure perception of teachers regarding both learning methods in teaching. The results showed a dominant preference for PBL as the selected method. Moreover, teachers also acknowledged a significant improvement in the learning outcomes of students. The contributions of PBL were twofold, 1) it promoted active learning by requiring students to take an active role during the learning process, and 2) it developed problem-solving skills by requiring the identification, analysis, and resolution of real-world problems.